Meaning and silence: notes for a phenomenology of the sielencio - González Hernández, Jorge Manuel (2022)
This paper aims to outline the principles of phenomenology of silence based on the texts Meaning without language and the task of phenomenology by Antonio Zirión Quijano and Maurice Merleau-Ponty's Phenomenology of perception. Our paper investigates what is known as the "limit zones" of phenomenology. It proposes a conception of its method that links the Husserlian roots of the method with the findings derived from our study of silence as a phenomenon given to consciousness. We will enunciate the features of what we have called the "phenomenology of silence", which focuses on reviewing the limited modalities of appearing. Thus, we will review what has been considered an issue that exceeds the scope of phenomenology since silence had been analysed only as "natural silence" (silence of absence) over subjective silence. Here we will discuss the belief that phenomenology only partially deals with regions of being and that its methodology is insufficient to explain the world as a whole when confronted with phenomena such as silence.